PENGENDALIAN PERSEDIAAN DAN PROSES PRODUKSI PENGARUHNYA TERHADAP KUALITAS PRODUK DI UKM KARYA ABADI PRABUMULIH - Heriyana Heriyana (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
This research entitled Inventory Control and Production Processes Its Effect on Product Quality in Karya Abadi Prabumulih UKM. The purpose of this research is first, to analyze the Inventory Control and Production Processes of the Effect Together on Product Quality. Second, analyze Inventory Control Influence on Product Quality. Third, the Production Process's Effect on the Quality of Produ in Karya Abadi Prabumulih UKM. The research design, this research is correlational which aims to examine the extent to which a variable on a factor is related to other variables. The design used uses a quantitative approach as one of the scientific search efforts (scientific inquiry) through the process of analysis using statistical techniques to reduce and classify data and determine relationships so as to produce a conclusion that can be generally accepted. The population in this study is the purchase of raw materials, production processes from UKM Abadi Abadi Prabumulih. This study is a study in which the population is converted into research samples. The research method used in this study is a quantitative method. The sampling criteria include, 1). Report on purchases of raw materials for the period January 2016 - December 2018. b). Monthly production report for the period 2016 - 2018. The results of this study are first, there is a significant influence of inventory control and production processes together on product quality. Second, there is no significant effect of inventory control on product quality. Third, there is a significant influence on the production process on product quality.